2004
DOI: 10.4049/jimmunol.172.2.981
|View full text |Cite
|
Sign up to set email alerts
|

A Switch in Costimulation from CD28 to 4-1BB during Primary versus Secondary CD8 T Cell Response to Influenza In Vivo

Abstract: 4-1BBL−/− mice exhibit normal primary CD8 T cell responses to influenza virus, but show decreased CD8 T cell numbers late in the primary response as well as decreased secondary responses. In contrast, CD28−/− mice are defective in initial CD8 T cell expansion. Using agonistic anti-4-1BB Ab to replace the CD28 or 4-1BB signal, we examined the timing of the required signals for CD28 vs 4-1BB costimulation. A single dose of agonistic anti-4-1BB Ab added only during priming restores the secondary CD8 T cell respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 53 publications
4
112
0
Order By: Relevance
“…However, i.p. infection of influenza virus in 4-1BBL Ϫ/Ϫ mice showed normal primary CD8 responses, but in this case with impaired memory formation (25)(26)(27). Collectively, these data suggest that OX40-OX40L and 4-1BB-4-1BBL interactions can provide enhancing signals, but their interaction is not always necessary to priming of CD8 T cells.…”
Section: Functional Dichotomy Between Ox40 and 4-1bb Inmentioning
confidence: 73%
See 1 more Smart Citation
“…However, i.p. infection of influenza virus in 4-1BBL Ϫ/Ϫ mice showed normal primary CD8 responses, but in this case with impaired memory formation (25)(26)(27). Collectively, these data suggest that OX40-OX40L and 4-1BB-4-1BBL interactions can provide enhancing signals, but their interaction is not always necessary to priming of CD8 T cells.…”
Section: Functional Dichotomy Between Ox40 and 4-1bb Inmentioning
confidence: 73%
“…In opposition to some of the experiments with anti-4-1BB, all studies of 4-1BBL Ϫ/Ϫ mice have either revealed no role for this ligand in initial CD8 priming, or suggested that 4-1BB/4-1BBL interactions play a positive, enhancing role, largely at a late stage of the CD8 T cell response when memory has formed or when memory is beginning to develop (23)(24)(25)(26)(27). Our studies represent the first to specifically address how the lack of 4-1BB on a CD8 cell affects its initial response and clearly show that without 4-1BB, CD8 cells are hyperresponsive to Ag in both primary and secondary responses, at least when provided via adenovirus.…”
Section: Discussionmentioning
confidence: 99%
“…[25]. These factors are also known to affect T memory/effector cell activation [26,27]. Consequently, one might expect that different antigen doses (constituting Signal 1) will be required for T cell triggering upon antigen recognition on different APC.…”
Section: Similar Per Cell Ifn-γ Productivity Of Cd4 Cells Stimulated mentioning
confidence: 99%
“…4-1BB can enhance both the proliferation and the survival of murine CD4 and CD8 T cells (8)(9)(10)(11)(12)(13)(14). Recent evidence in mouse models suggests that 4-1BB͞4-1BBL interaction plays an important role in the memory CD8 T cell response to viruses (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…In view of the evidence in mice that 4-1BBL is important in CD8 T cell memory (18), we set out to directly test the ability of 4-1BBL to stimulate antiviral cytotoxic memory T cells from humans. The results show that 4-1BBL-mediated costimulation is highly effective in expanding and activating T cell memory responses to influenza virus and Epstein-Barr virus (EBV) and does so with faster kinetics than B7.1.…”
mentioning
confidence: 99%